2020
DOI: 10.1186/s12935-019-1090-9
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor protein LNK promotes anaplastic thyroid carcinoma cell growth via 14-3-3 ε/γ binding

Abstract: Background: Rapid progression contributes to treatment failure in anaplastic thyroid carcinoma (ATC) patients. In a preliminary study, we demonstrated that some hematopoietic factors may be involved in the progression of ATC. The adaptor protein LNK, which is a negative regulator of hematopoietic cytokine signalling, has been studied extensively in malignant hematopoietic cells. However, there are few studies on LNK in solid tumours. Methods: Real-time PCR, immunohistochemistry (IHC) and western blot analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…On the other hand, SH2B3 was reported to play paradoxical roles in solid tumor initiation and progression. On the contrary, previous studies show that SH2B3 promotes Jak/STAT signaling in myeloproliferative neoplasms (Oh et al, 2010) and promotes ovarian cancer (Ding et al, 2015), breast cancer (Lv et al, 2020), and anaplastic thyroid carcinoma (Zhong et al, 2020) progression. The biological function of FIGURE 9 | Working model.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, SH2B3 was reported to play paradoxical roles in solid tumor initiation and progression. On the contrary, previous studies show that SH2B3 promotes Jak/STAT signaling in myeloproliferative neoplasms (Oh et al, 2010) and promotes ovarian cancer (Ding et al, 2015), breast cancer (Lv et al, 2020), and anaplastic thyroid carcinoma (Zhong et al, 2020) progression. The biological function of FIGURE 9 | Working model.…”
Section: Discussionmentioning
confidence: 89%
“…Although SH2B3 is considered to act as a negative regulator in hematological cancer, its role in solid tumors remains controversial. SH2B3 was reported to act as a tumor promoter in ovarian ( 84 ), breast ( 85 ) and anaplastic thyroid cancer ( 86 ) cancer. However, compared with matched adjacent normal tissues, SH2B3 was found to be downregulated in colon cancer, and its overexpression led to a decrease in the invasion rate of colon cancer cells ( 87 ).…”
Section: Role Of Stat3 Signaling In Emtmentioning
confidence: 99%
“…By studying human melanoma tissue arrays and mRNA expression data from available databases, Ding et al found that LNK is overexpressed in patients with melanoma, and that higher expression of LNK is associated with shorter overall survival [127]. Likewise, elevated expression of LNK was detected in patients with thyroid carcinoma [128]. In glioblastoma patients, elevated expression of LNK predicted worse survival [129].…”
Section: Lnk In Hormone Receptor-positive Breast Cancermentioning
confidence: 99%
“…Interestingly, functional analysis in cell lines has also shown that LNK-associated activities seem to depend upon cell type. For instance, the induction of LNK overexpression in thyroid carcinoma-derived [128] and glioblastomaderived [129] cell lines resulted in increased cell proliferation and migration, as well as protection against apoptosis. These observations agree with clinical data showing an association between LNK overexpression and poor survival in glioblastoma patients [129].…”
Section: Lnk In Hormone Receptor-positive Breast Cancermentioning
confidence: 99%